Atypical femoral fractures - Cheung, Angela (Henry Stewart Talks, 2016)
AFF definition and key clinical features, Pharmacological therapy and considerations, Imaging: x-rays and other modalities, Epidemiology, Risk factors, Diagnosis, management and recommendations, Incomplete AFF, Fracture healing, Prevention: rethinking osteoporosis paradigm, Assessment of fracture risk